Exceeding expectations: A study on human resource management implementation in construction organisations - Munodani Chapano; Chux G. Iwu (SA Journal of Human Resource Management, 2025)
Orientation: Human resource management (HRM) professionals and organisational leaders may maximise the performance of construction organisations by thoroughly understanding the implementation of HRM practices within these businesses.